The Development of Banjar-Based e-Parenting Education Model in Improving Adaptive Behaviour of Elementary School Children - Ni Luh Sulisnadewi; I Ketut Gama; I Ketut Labir (Babali Nursing Research, 2023)
Introduction. Parenting during the COVID-19 pandemic is a challenge that needs to be addressed. Behaviour change as a result of restrictions requires that children and parents must adapt. For this reason, a parenting model is needed so that the process of behavioural education in children by parents continues and is able to be adapted by children. Objective. This research was conducted to find a parenting model during a pandemic so that children are adaptive in playing, learning, doing PHBS and conducting social interactions. Methods This study was an exploratory and experimental study with subjects of parents and children with a control group of 60 and treatment of 63. This research was conducted in Denpasar, Gianyar and Klungkung. The data were analysed by t-test. Result. The results of the analysis showed that there were differences in parenting abilities in mothers who were educated with digital modules with p = 0.00. Digital parenting in mothers has a good influence on children's adaptation in playing p=0.00, in learning 0.00 and socialization p= 0.006, but not significantly to PHBS p= 0.177 at p (<0.005). This means that during a pandemic, digital education is very appropriate to improve maternal parenting for children to adapt to a pandemic situation. Conclusions. Good parenting knowledge is very significant in improving children's adaptability to play, learn and socialize. For this reason, during a pandemic, digital parenting education is very appropriate to do.